Globalization and financial crisis : a dynamic approach - Gravier-Rymaszewska, Joanna (2013)
This dissertation investigates some of the outcomes of globalization, exploring the effects and transmission of shocks between countries. It consists of three essays interconnected by the topic of globalization and economic crises.